Serum creatinine, cystatin C, and beta-trace protein in diagnostic staging and predicting progression of primary nondiabetic chronic kidney disease - Spanaus, Katharina-Susanne; Kollerits, Barbara; Ritz, Eberhard; Hersberger, Martin; Kronenberg, Florian; Eckardstein, Arnold von (Clinical chemistry, 2010)
BACKGROUND: Impaired baseline kidney function is a well-defined risk factor for progression of chronic kidney disease (CKD). We evaluated measured glomerular filtration rate (GFR) and the serum markers creatinine, cystatin C, and beta-trace protein (BTP) for diagnostic accuracy in defining the stage of kidney impairment and as risk predictors of CKD progression. - METHODS: We measured serum marker concentrations in 227 patients with primary nondiabetic CKD and various degrees of renal impairment and followed 177 patients prospectively for up to 7 years to assess progression of CKD. - RESULTS: At baseline, creatinine, cystatin C, and BTP were strongly correlated with GFR as measured by iohexol clearance. Concentrations of all 3 markers increased progressively with decreasing GFR, and their diagnostic performance for the detection of even minor deteriorations of renal function (GFR <90 mL x min(-1) x (1.73 m(2))(-1)) was similar. Sixty-five patients experienced progression of CKD, defined as doubling of baseline creatinine and/or terminal renal failure during prospective follow-up. These patients were older and had a lower GFR and higher serum creatinine, cystatin C, and BTP values at baseline (all P < 0.001) compared with the patients who did not reach a predefined renal endpoint. Cox proportional hazard regression analysis revealed that all 3 clearance markers were equally strong predictors of CKD progression, even after adjustment for age, sex, GFR, and proteinuria. - CONCLUSIONS: The diagnostic performance of serum creatinine, cystatin C, or BTP for detecting even minor degrees of deterioration of renal function is good, and these markers provide reliable risk prediction for progression of kidney disease in patients with CKD.